Plant–arthropod interactions of an endangered California lupine - Motta, Carina I. [UNESP]; Luong, Justin C.; Seltmann, Katja C. (Wiley, 2022)
The reintroduction of endangered plant species is an essential conservation tool. Reintroductions can fail to create resilient, self-sustaining populations due to a poor understanding of environmental factors that limit or promote plant success. Biotic factors, specifically plant–arthropod interactions, have been shown to affect the establishment of endangered plant populations. Lupinus nipomensis (Nipomo Mesa lupine) is a state of California (California Rare Plant Rank: 1B.1) and federally (65 FR 14888) endangered endemic plant with only one extant population located along the central California coast. How arthropods positively or negatively interact with L. nipomensis is not well known and more information could aid conservation efforts. We conducted arthropod surveys of the entire L. nipomensis extant population in spring 2017. Observed arthropods present on L. nipomensis included 17 families, with a majority of individuals belonging to Thripidae. We did not detect any obvious pollinators of L. nipomensis, providing support for previous studies suggesting this lupine is capable of self-pollinating, and observed several arthropod genera that could potentially impact the reproductive success of L. nipomensis via incidental pollination or plant predation.
Keywords: coastal dune; endemic; Fabaceae; Lupinus nipomensis; pollination; restoration